Atezolizumab-Induced Acrodermatitis and Pustular Psoriasis in a Patient with Non-Small Cell Lung Cancer: A Rare Case Report - Davide Fattore; Gianluca Esposito; Ludovica Carangelo; Maria Antonietta Luciano; Matteo Megna (Karger Publishers, 2024)
Introduction: Immune checkpoint inhibitors are new drugs approved for the treatment of many types of malignancies. Despite their wide use and unquestionable clinical benefits, these agents have also been associated with a unique spectrum of side effects known as immune-related adverse events. In this study, we report the first case of atezolizumab-induced pustular psoriasis and acrodermatitis. Case Presentation: A 61-year-old woman presented to our department with erythematous-desquamative and pustular lesions involving all hands and feet fingers, inguinal region, and trunk, associated to severe psoriatic onychodystrophy. She was affected by non-small-cell lung carcinoma from 12 years, and 7 months before admission, she started a treatment with atezolizumab. Conclusion: Immune checkpoint inhibitors such as atezolizumab are linked to a plethora of adverse events. Identifying and treating certain adverse skin events, particularly in cancer patients, can be a challenge, leading oncologists to discontinue immunotherapy. Our case shows how it is necessary to have a shared therapeutic algorithm in order to manage serious skin reactions in cancer patients and avoid disruption of the oncotherapy.